Pengaruh Gaya Belajar dan Pemanfaatan Sumber Belajar terhadap Hasil Belajar PPKn Siswa - Rizky Yuniarsih; Kamaludin Kamaludin (JOEAI:Journal of Education and Instruction, 2021)
The purpose of this study was to determine the effect of learning styles and the use of learning resources on the learning outcomes of fifth grade Civics at SD Negeri Sekbin II, Bulakamba District, Brebes Regency. 168 students have been selected to be the sample of the study by means of random sampling and the solvin formula. The results of the study found that; (1) There is an influence between learning styles on PPKn learning outcomes with the results of the calculation of tcount > ttable which is 4, 039 > 1,974 and the correlation between the two is 0.299 or is said to be in the low category. The contribution of learning styles to student Civics learning outcomes is 8.9%; (2) There is an influence between the use of learning resources on PPKn learning outcomes with the results of the calculation of tcount > ttable which is 6.405 > 1.974 and the correlation between the two is 0.445 or is said to have a relationship in the medium category. The contribution of the use of learning resources to students' Civic Education learning outcomes is 19.8%; (3) There is an influence between learning style and the use of learning resources on students' Civic Education learning outcomes with the results of the calculation Fcount > Ftable, namely 25.07 > 3.051 and multiple correlation in the medium category (0.483). The contribution of learning styles and use of learning resources to student Civic Education learning outcomes is 23.3%. In conclusion, there is a statistically significant effect of learning style and the use of learning resources on the learning outcomes of fifth grade Civics at SD Negeri Sekbin II, Bulakamba District, Brebes Regency. Keywords: Learning Style, Learning Outcomes, Utilization of Learning Resources, PPkn